2014
DOI: 10.1016/j.buildenv.2013.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Buoyant flows in street canyons: Validation of CFD simulations with wind tunnel measurements

Abstract: Computational fluid dynamics (CFD) is often used to predict flow structures in urban areas for the determination of pollutant dispersion, human comfort or heat fluxes. During daytime building façades and ground surfaces are heated by solar radiation and thereby induce buoyancy, which changes the flow field around buildings significantly. The CFD models used to simulate buoyant flow fields in urban areas are not sufficiently validated. This study aims to validate CFD simulations for buoyant flows in urban stree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 32 publications
(43 reference statements)
4
62
0
Order By: Relevance
“…Allegrini et al [2] have conducted the validation of FLUENT using 2-D steady RANS simulations for the case of a heated street-canyon under a background wind as characterized by different Froud and Reynolds numbers. For the validation mean velocity and turbulent kinetic energy were assessed.…”
Section: Flow and Heat Transfer Over A Heated Street-canyonmentioning
confidence: 99%
“…Allegrini et al [2] have conducted the validation of FLUENT using 2-D steady RANS simulations for the case of a heated street-canyon under a background wind as characterized by different Froud and Reynolds numbers. For the validation mean velocity and turbulent kinetic energy were assessed.…”
Section: Flow and Heat Transfer Over A Heated Street-canyonmentioning
confidence: 99%
“…e choice of a 2D model allows lower computational costs without compromising the accuracy of the results [14][15][16][17][18]. In order to test the e ectiveness of this choice, both the 3D and 2D models have been run and compared with the experimental data.…”
Section: Geometry and Numerical Domainmentioning
confidence: 99%
“…ey observed that short-time variations of wind velocity can greatly influence the mass transfer rate between the canyon and the overlying boundary layer. Allegrini et al [17] carried out 2D steady RANS simulations with different near-wall treatments in order to validate numerical results for buoyant flows in urban street canyons by comparison with wind-tunnel measurements. ey compared the results of different turbulence models (STD k-ε, realizable k-ε, k-ω, Spalart-Allmaras, and Reynolds stress model (RSM)), showing a better agreement of the STD k-ε model with the NEWFs (nonequilibrium wall functions) than the LRNM (low-Reynolds number modeling).…”
Section: Introductionmentioning
confidence: 99%
“…Its flow regimes are mainly determined by canyon geometry, ambient wind condition, atmospheric instabilities, and building layout (Vardoulakis et al, 2003;Georgakis and Santamouris, 2004). Many field measurements, laboratory experiments and numerical simulations have been conducted based on different meteorological and geometrical factors (Li et al, 2006;Allegrini et al, 2014). Richards et al (2006) conducted a stratified wind tunnel experiment to analyze the thermal effects of leeward wall heating; he concluded that cavity eddies tend to be strong with ground heating.…”
Section: Introductionmentioning
confidence: 99%